"Preventive" pacing in patients with tachy‐brady syndrome (TBS): Confirming a common practice. Issue 10 (29th June 2020) - Amir, Teva; Ilan, Michael; Fishman, Euvgeny; Michowitz, Yoav; Khalameizer, Vladimir; Katz, Amos; Glikson, Michael; Medina, Aharon; Rav Acha, Moshe
Abstract: Aims: Many tachy‐brady syndrome (TBS) patients, are implanted a permanent pacemaker (PPM) to allow continuation of anti‐arrhythmic drug (AAD) therapy to maintain sinus rhythm. Many of these PPM's are implanted as a preventive measure, in absence of symptomatic bradycardia. Our primary aim was to evaluate pacing use among these patients and find predictors for PPM use. Our secondary aim was to appreciate the portion of these patients who progress to permanent atrial fibrillation (AF). Methods: Retrospective study of TBS patients implanted a PPM as preventive measure, dividing cases into defined categories regarding highest percent atrial and ventricular pacing documented in PPM clinic visits during 3 year follow‐up (F/U) period. Patients' baseline characteristics and AAD therapy were compared between cases with a major (>90%) pacing use and cases with <90% pacing use to find predictors for pacing use. Multivariable logistic regression was applied to identify independent variables associated with major pacing use. Results: Our study included 119 TBS patients. Most (86.5%) TBS patients had a moderate (>50%) pacing use and 58% had a major pacing use. Significant association was found between pre‐implant severe sinus bradycardia (<40 bpm), first degree atrioventricular block and amiodarone treatment to major pacing use on univariate analysis and severe sinus bradycardia was significantly associated with major pacing on multivariate analysis as well. Only minority (16.8%) of TBS patients progressed to permanent AF during the study F/U period. Conclusion: Our study reveals most TBS patients succeed to maintain sinus rhythm using an AAD with a significant pacing use, suggesting preventive PPM implantation might be advantageous in these cases. Pre‐implant severe sinus bradycardia (<40 bpm) is a possible predictor for major pacing use in this population.